Swearing in English : bad language, purity and power from 1586 to the present - McEnery, Tony, 1964- (Routledge advances in corpus linguistics ;, 2006)
Swearing is an everyday part of the language of most speakers of modern English. This corpus informed account of swearing describes swearing and its social function, with a particular focus on the relationship between swearing and abuse.